Peculiar type 1 congenital pyloric atresia: a case report - Nanni Lorenzo; Pintus Claudio; Corsello Mirta; Zecca Enrico; Zecca Susanna (BMC, 2010)
Abstract Pyloric atresia (PA) is a very rare condition. Its incidence is approximately 1 in 100,000 newborns and constitutes about 1% of all intestinal atresias. We describe the neonatal course of a peculiar case of type 1 pyloric atresia, in which the pyloric membrane was connected to a second duodenal membrane through a virtual duodenal lumen in a premature newborn. The atypical variant required an unusual side to side gastroduodenostomy. We emphasize the importance of a prompt diagnosis to avoid potentially fatal complications and to warrant a good outcome even in the presence of a strange form of PA in the neonatal period.